Sozialpädagogik als Lösung in der Prävention von sozial-pathologischen Erscheinungen in der Schule - Smetanová, Dorota; Koldeová, Lujza (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2013)
The paper presents the basic definition of social pedagogy as a pedagogical discipline. It also focuses on the opportunities and challenges of social pedagogy in the prevention of socio-pathological phenomena. It asks the following questions-Is social pedagogy able to timely and professional assistance to ensure? Needs company a social practice of teachers?